Review: Pemanfaatan Obat Herbal pada Penyakit Alzheimer dari Tiga Tanaman di Indonesia - Pangalila, Anggelina Aprilia (STIKes Medistra Indonesia, 2023)
Alzheimer's disease is a disease in which brain damage is characterized by a decrease in attention, memory, and personality. Personality changes often occur when sufferers become less spontaneous, more apathetic, and withdrawn from their environment. The use of chemical drugs derived from the synthesis of natural drugs is approved for clinical use for Alzheimer's patients. Synthesis from natural materials is carried out because of the many chemical compounds contained in plants which have various biological and pharmacological effects. As for the use of natural medicines that are efficacious as antioxidants, anticoagulants, and anti-inflammatories, they are targets in the prevention of Alzheimer's disease where from these effects they can inhibit the acetylcholinesterase enzyme that plays a role in neurotransmitter damage. This journal review aims to maximize the use of natural medicines that have antioxidant effects from plants such as turmeric (Curcuma longa L.), gotu kola (Centella asiatica L.) and Kelor leaves (Moringa oleifera Lam.) so that these three plants are expected to have an effect. potential in the prevention of Alzheimer's disease which will be discussed extensively.